EFEKTIFITAS AIR REBUSAN JAHE MERAH (Zingiber Officinale Var Rubrum) DAN AKUPRESUR LV3 TERHADAP PENURUNAN DISMENOREA PADA REMAJA - Khusnul Khotimah; Desta Ayu Cahya Rosyida; Anik Latifah; Tetty Rihardini (Rena Cipta Mandiri, 2025)
Background: Dysmenorrhoea is a common menstrual pain complaint among adolescents that may interfere with daily activities. Non-pharmacological therapies such as red ginger decoction and LV3 acupressure are considered effective, safe, and affordable alternatives. Objective: To determine the effectiveness of combining red ginger decoction and LV3 acupressure in reducing dysmenorrhoea among adolescents. Methods: This pre-experimental study applied a one group pre-test–post-test design with 30 female students from Nurusshaleh MTs and Senior High School, Katol Timur, Kokop Sub-district, Bangkalan, Madura. Interventions were given for two consecutive days: red ginger decoction twice daily and LV3 acupressure once daily. Pain intensity was assessed using the Numeric Rating Scale (NRS). Results: The Wilcoxon signed-rank test showed a significant reduction in pain (p=0.000). Before intervention, most respondents reported moderate (43.3%) and severe pain (46.7%). After intervention, 70.0% reported mild pain and 30.0% reported no pain. Conclusion: Gingerol in red ginger has anti-inflammatory and anticoagulant properties, while LV3 acupressure stimulates endorphin release. The combination effectively reduces dysmenorrhoea and can be recommended as an alternative therapy that is practical, inexpensive, and self-applicable.